Heat press cushioning parts
By using a combination of fluoroelastomer, vulcanizing agent, acid absorbing agent and dehydrating agent in the hot pressing buffer, the problems of heat disk corrosion and buffering at high temperatures are solved, and higher heat resistance and service life are achieved.
Patent Information
- Application Number
- CN202080062443.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-29
- Filing Date
- 2020-10-27
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-10-27
AI Technical Summary
The existing hot pressing buffer parts may cause corrosion of the hot disk when used at high temperatures, and the buffering ability decreases after repeated use, making it difficult to meet the heat resistance requirements at high temperatures.
Using a hot press buffer containing fluoroelastomer, vulcanizing agent, acid absorbing agent and dehydrating agent, the hydrogen fluoride gas and dehydrating agent generated by neutralizing the acid absorbing agent to absorb moisture in the fluoroelastomer, and optimize the proportion of the composition to improve heat resistance. and buffering.
It effectively suppresses corrosion of the hot disk and maintains the buffering properties of the buffer parts when repeatedly used at high temperatures, extending the service life.
Smart Images

Figure CN114364501B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hot pressing buffer. More specifically, the present invention relates to a hot pressing buffer used when stamping and hot pressing the target product in the process of manufacturing a copper-clad laminate, a flexible printed substrate, a rigid-flexible substrate, a multilayer board, a multilayer flexible printed substrate and other printed substrates, an insulating board, a credit card, an IC card, a liquid crystal display panel, a ceramic laminate and other precision equipment parts, a melamine decorative board, etc. (hereinafter referred to as a "laminated board" in the present invention). Background Art
[0002] In the manufacture of laminated boards such as printed circuit boards, in the stamping and thermocompression processes, Figure 3 As shown in the figure, a laminated plate material 12 as a stamping object is sandwiched between hot plates 13, 13 as a heating / pressing mechanism and a certain pressure and heat are applied. In order to obtain a high-precision formed product, it is necessary to make the heat and pressure applied to the laminated plate material 12 uniform over the entire surface during hot pressing. For this purpose, hot pressing is performed in a state where a flat buffer 11 is sandwiched between the hot plate 13 and the laminated plate material 12. It should be noted that a stainless steel mirror plate is sometimes also sandwiched between the buffer 11 and the laminated plate material 12.
[0003] Here, as general properties required of the buffer part 11, there can be listed the buffering property for absorbing the unevenness of the hot plate 13 and the laminated plate material 12, the in-plane uniformity for uniformly transferring the temperature and pressure from the hot plate 13 to the laminated plate material 12 throughout the entire stamping surface, the heat conductivity for efficiently transferring heat from the hot plate 13 to the laminated plate material 12, the heat resistance that can withstand the stamping temperature, etc.
[0004] As such a buffer, a component using synthetic rubber may be provided. Its typical structure is a structure in which a layer of woven or non-woven fabric composed of heat-resistant fibers such as glass fiber and aromatic polyamide fiber is combined with a synthetic rubber layer to be laminated and integrated. In addition, there is known a structure in which a surface layer such as a fluororesin film is bonded and integrated to the surface of the buffer in order to make them have demoulding properties.
[0005] As such a buffer, for example, Japanese Patent Application Laid-Open No. 6-278153 (Patent Document 1) discloses a forming press buffer having a buffer body having a fluororubber layer and a surface layer, wherein the fluororubber layer contains a fluororubber raw material, an acid absorber, and a vulcanizing agent.
[0006] Prior Art Literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 6-278153 Summary of the invention
[0009] Summary of the Invention
[0010] Problems to be solved by the invention
[0011] The forming press cushioning material of Patent Document 1 uses an acid absorber and a vulcanizing agent to improve heat resistance, but there is a need to further improve heat resistance.
[0012] When the forming press buffer of Patent Document 1 is used at high temperatures, hydrogen fluoride (corrosive gas) is generated from the fluororubber during use, which may cause corrosion of the hot plate. Therefore, in order to suppress the generation of hydrogen fluoride, the forming press buffer of Patent Document 1 contains a large amount of acid absorbent in the fluororubber. However, even if a large amount of acid absorbent is contained in the fluororubber, the hot plate may sometimes be corroded when used at high temperatures such as 230°C to 250°C. Moreover, when the forming press buffer of Patent Document 1 is repeatedly used at high temperatures, the cushioning properties may sometimes be significantly reduced.
[0013] The present invention is made to solve the above-mentioned problems, and its purpose is to provide a hot pressing buffer that can improve heat resistance. Specifically, first, the hot pressing buffer can suppress corrosion of the hot plate even when used at high temperatures, and second, the hot pressing buffer can suppress the decrease in cushioning properties even when used repeatedly at high temperatures.
[0014] Solutions to Solve Problems
[0015] A hot press buffer according to one embodiment of the present invention is a hot press buffer comprising fluororubber, wherein the composition of the fluororubber comprises a fluororubber component, a vulcanizing agent, an acid absorber, and a dehydrating agent. The acid absorber has a function of neutralizing hydrogen fluoride generated by the deterioration of the fluororubber and causing the hot plate to corrode. The dehydrating agent has a function of absorbing water contained in the fluororubber.
[0016] Preferably, the amount of the dehydrating agent is larger than the amount of the acid acceptor based on 100 parts by mass of the total of the fluororubber component and the vulcanizing agent.
[0017] It is preferable that the amount of the dehydrating agent relative to 100 parts by mass of the total of the fluororubber component and the vulcanizing agent is 1.5 times or more the amount of the acid acceptor.
[0018] Preferably, the total amount of the acid acceptor and the dehydrating agent is 3 to 50 parts by mass based on 100 parts by mass of the total of the fluororubber component and the vulcanizing agent.
[0019] Preferably, the acid absorber includes at least one selected from the group consisting of magnesium oxide, zinc oxide, lead oxide, dibasic lead phosphate and hydrotalcite.
[0020] Preferably, the dehydrating agent includes at least one selected from the group consisting of calcium oxide, aluminum oxide, magnesium sulfate, and magnesium chloride.
[0021] Preferably, the acid absorber is magnesium oxide and the dehydrating agent is calcium oxide.
[0022] Preferably, the mass ratio of magnesium oxide to calcium oxide is magnesium oxide:calcium oxide=1:4 to 2:3.
[0023] Preferably, the BET specific surface area of magnesium oxide is 80 m 2 / g and above and 300m 2 More preferably, the BET specific surface area of magnesium oxide is 100 m 2 / g and above 260m 2 / g or less.
[0024] Preferably, the heat-resistant temperature of the hot-pressing buffer material is 250° C. or higher and 300° C. or lower.
[0025] Effects of the Invention
[0026] According to the present invention, heat resistance can be improved. Specifically, first, corrosion of the hot plate can be suppressed even when used at high temperatures, and second, a decrease in cushioning properties can be suppressed even when used repeatedly at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram which shows the cushioning material for hot pressing which is embodiment of this invention.
[0028] Figure 2 The top views of the iron plates in the examples are shown, (A) showing a state where no corrosion or discoloration is observed on the iron plate, (B) showing a state where corrosion or discoloration is observed on the hot plate, and (C) showing a state where rust has progressed to the inside of the iron plate and corrosion or missing parts are observed.
[0029] Figure 3 It is a diagram for explaining the hot pressing process. DETAILED DESCRIPTION
[0030] The embodiments of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the same or corresponding parts in the drawings are denoted by the same reference numerals and their description is omitted.
[0031] <Hot Press Cushioning Parts>
[0032] Figure 1 (A) to (D) show specific configuration examples of the hot press cushioning material of this embodiment. Figure 1(A) to (D) of FIG. 1 describe configuration examples of the hot press cushioning materials 1A to 1D of the present embodiment. The hot press cushioning materials 1A to 1D of the present embodiment are made of fluororubber.
[0033] Figure 1 The hot press cushioning material 1A shown in (A) is a fluororubber sheet consisting only of a fluororubber layer 2. It should be noted that a surface layer consisting of paper, woven fabric, nonwoven fabric, synthetic resin film or the like may be laminated on the surface and back of the fluororubber layer 2.
[0034] Figure 1 The hot press cushioning member 1B shown in (B) comprises: a nonwoven fabric layer 3 formed of a nonwoven fabric; two fluororubber layers 2 sandwiching the nonwoven fabric layer 3 from above and below; and a surface layer 4 formed of a synthetic resin film and attached to the front and back surfaces of the two fluororubber layers 2.
[0035] Figure 1 The hot press cushioning member 1C shown in (C) comprises: a base layer 5 of a fiber-rubber composite material in which fluororubber is impregnated in a woven fabric; and a surface layer 4 formed of a synthetic resin film and attached to the front and back surfaces of the base layer 5 of the fiber-rubber composite material. It should be noted that the fiber-rubber composite material of the base layer 5 contains fluororubber.
[0036] Figure 1 The hot press cushioning member 1D shown in (D) comprises: two base layers 5 of a fiber-rubber composite material; an adhesive layer 6 formed of fluororubber and bonding the two base layers 5; and a surface layer 4 formed of a synthetic resin film and attached to the front and back surfaces of the two base layers 5. It should be noted that the fiber-rubber composite material of the base layer 5 and the adhesive layer 6 contain fluororubber.
[0037] Such hot press cushioning materials 1A to 1D can be used at high temperatures, and their heat-resistant temperature is 250° C. to 300° C. If the use temperature exceeds 300° C., the cushioning properties may be significantly reduced in the case of repeated use.
[0038] Thus, the fluororubber of this embodiment includes, for example, a fluororubber sheet, a fluororubber impregnated in a substrate, a fluororubber adhesive, etc. That is, the fluororubber does not have to be a single layer, but can be impregnated or attached to a fiber, etc. It should be noted that, Figure 1 The hot press cushioning materials 1A to 1D of (A) to (D) are examples, and any material may be provided with the fluororubber structure described below, and are not limited to the above structure.
[0039] Next, the fluororubber used in the hot press cushioning member will be described in detail.
[0040] <Fluororubber>
[0041] The composition of fluororubber includes a fluororubber component as a base material, a vulcanizing agent, an acid absorbent, and a dehydrating agent.
[0042] The fluororubber component includes various components such as fluorinated acrylate polymers, vinylidene fluoride copolymers, fluorinated silicone rubbers, fluorinated polyester rubbers, and fluorinated diene copolymers, but the type thereof is not particularly limited and can be appropriately selected from these components for use.
[0043] As the vulcanizing agent, a material known as a vulcanizing agent for fluororubber, such as an organic peroxide vulcanizing agent, an amine vulcanizing agent, and a polyol vulcanizing agent, can be used. The vulcanizing agent is a formulation agent for vulcanizing fluororubber.
[0044] Generally, an acid absorber is added to fluororubber in order to neutralize hydrogen fluoride generated during vulcanization reaction and promote vulcanization. However, when fluororubber is used for a hot press buffer, hydrogen fluoride is also generated during use due to use at high temperature, which may cause a decrease in the physical properties of the rubber and corrosion of the hot plate. Therefore, in this embodiment, an acid absorber is added in order to neutralize hydrogen fluoride generated not only during vulcanization but also during use.
[0045] The acid acceptor is selected from the group consisting of, for example, magnesium oxide, zinc oxide, lead oxide, dibasic lead phosphate and hydrotalcite. Only one type of the acid acceptor may be used, or two or more types of the acid acceptors may be used in combination. In particular, magnesium oxide is preferably used as the acid acceptor.
[0046] When magnesium oxide is used as the acid scavenger, it is preferred to use a magnesium oxide having a BET specific surface area of 80 m 2 / g and above and 300m 2 / g or less highly active magnesium oxide. The magnesium oxide preferably has a BET specific surface area of 100m 2 / g and above 260m 2 / g or less. BET specific surface area is 80m 2 / g or more of magnesium oxide is highly active, so it has a great effect in neutralizing hydrogen fluoride generated when using a hot press buffer. 2 / g, the dispersibility into fluororubber may decrease. It should be noted that the BET specific surface area is less than 80m 2 / g of magnesium oxide is low-activity magnesium oxide.
[0047] The dehydrating agent absorbs the water contained in the fluororubber. The dehydrating agent is selected from the group consisting of, for example, calcium oxide, aluminum oxide, magnesium sulfate, and magnesium chloride. Only one dehydrating agent may be used, but two or more dehydrating agents may be used in combination. In particular, the dehydrating agent is preferably calcium oxide. When calcium oxide is used as the dehydrating agent, it is preferably powdered calcium oxide with a small particle size.
[0048] The inventors have repeatedly studied the causes of hot plate corrosion and found that it is not sufficient to simply prepare an acid absorber to prevent hot plate corrosion, and that hot plate corrosion is largely related to the moisture in fluororubber. Therefore, it was discovered that a dehydrating agent is used to remove the moisture in fluororubber.
[0049] The ratio of the total amount of the acid absorber and the dehydrating agent to 100 parts by mass of the total of the fluororubber component and the vulcanizing agent is preferably 3 to 50 parts by mass, and more preferably 10 to 30 parts by mass. When the total amount of the acid absorber and the dehydrating agent is less than 3 parts by mass, it may sometimes cause a decrease in the physical properties of the rubber and corrosion of the hot plate. Moreover, when the total amount of the acid absorber and the dehydrating agent is more than 50 parts by mass, the preferred physical properties of the fluororubber, i.e., good physical properties such as cushioning and heat resistance, cannot be obtained, and the processability deteriorates.
[0050] The amount of the dehydrating agent relative to 100 parts by mass of the total of the fluororubber component and the vulcanizing agent is preferably more than the amount of the acid acceptor. Specifically, the amount of the dehydrating agent is preferably more than 1.5 times the amount of the acid acceptor. If the amount of the dehydrating agent relative to 100 parts by mass of the total of the fluororubber component and the vulcanizing agent is less than 1.5 times the amount of the acid acceptor, the dehydrating agent cannot fully absorb the moisture in the fluororubber, and the hot plate may sometimes corrode.
[0051] When magnesium oxide is used as the acid absorbent and calcium oxide is used as the dehydrating agent, the mass ratio of magnesium oxide to calcium oxide is more preferably magnesium oxide:calcium oxide=1:4 to 2:3.
[0052] As described above, the fluororubber composition in this embodiment includes a fluororubber component, a vulcanizing agent, an acid absorbent, and a dehydrating agent. The heat-resistant temperature of the conventional hot-pressing buffer is 230°C to 250°C, and it can only be used below this temperature. However, by using the fluororubber composition of this embodiment, it can be used even at high temperatures such as 250°C to 300°C, and the heat resistance can be improved.
[0053] Specifically, as a first effect, the use of the fluororubber composition of the present embodiment can suppress corrosion of the hot plate. This is believed to be because the acid absorber can suppress the generation of hydrogen fluoride (corrosive gas) when the hot press buffer is used at high temperature and the dehydrating agent can remove moisture in the fluororubber.
[0054] In addition, the cause of corrosion of the hot plate is greatly affected by the water content in the fluororubber. Therefore, rather than simply mixing the acid absorber and the dehydrating agent, the amount of the dehydrating agent is made larger than the amount of the acid absorber, thereby further suppressing the corrosion of the hot plate. Specifically, by setting the amount of the dehydrating agent to 1.5 times or more of the amount of the acid absorber relative to 100 parts by mass of the total of the fluororubber component and the vulcanizing agent, the corrosion of the hot plate can be effectively suppressed.
[0055] As a second effect, by using the fluororubber composition of the present embodiment, the cushioning properties of the hot press cushioning material can be maintained.
[0056] When the hot plate is coated with an anti-corrosion coating, there is no need to consider the corrosion of the hot plate. However, the hot press buffer of this embodiment has buffering properties even when used repeatedly at high temperatures, and can be effectively used for hot pressing where there is no need to consider the corrosion of the hot plate.
[0057] For example, vulcanization accelerators, plasticizers, fillers, etc. may be arbitrarily formulated into fluororubber.
[0058] Example
[0059] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited thereto.
[0060] <Corrosion test related to hot plate>
[0061] Table 1 shows the mass ratio of each raw material in Examples 1 to 5, and Table 2 shows the mass ratio of each raw material in Comparative Examples 1 to 5. Table 3 specifically shows each raw material in Table 1 and Table 2. Table 4 shows the results of the corrosion test on the hot plate.
[0062] (Example 1)
[0063] First, the raw materials of the fluororubber sheet, i.e., fluororubber as the raw material of the base material, an acid absorber, a dehydrating agent, and a vulcanization accelerator were prepared. For the raw material fluororubber DAI-EL G-716, an appropriate amount of polyol vulcanizing agent was pre-mixed in the fluororubber component. As the acid absorber, Kyowamag MF-150 (BET specific surface area 119 m 2 / g). Calcium oxide was used as a dehydrating agent.
[0064] These raw materials were mixed in the ratio shown in Table 1 and vulcanized at 185°C for 30 minutes under a pressure of 10 MPa. As a secondary vulcanization, heating was performed at 230°C for 5 hours without pressure to produce a fluororubber sheet with a size of 250 mm×250 mm and a thickness of 2 mm.
[0065] (Example 2)
[0066] The method for producing the fluororubber sheet of Example 2 is basically the same as that of Example 1, but calcium oxide used as a dehydrating agent is different as shown in Tables 1 and 3 below.
[0067] (Example 3)
[0068] The method for preparing the fluororubber sheet of Example 3 is basically the same as that of Example 1, but as shown in Table 1 below, the difference is that Magsarat #30 (BET specific surface area 42 m 2 / g) as an acid absorber.
[0069] (Example 4)
[0070] The method for producing the fluororubber sheet of Example 4 is basically the same as that of Example 1. Although the same raw materials as those of Example 1 are used, the mass ratio of highly active magnesium oxide as an acid absorber and calcium oxide as a dehydrating agent is different as shown in Table 1 below.
[0071] (Example 5)
[0072] The method for producing the fluororubber sheet of Example 5 is basically the same as that of Example 1. Although the same raw materials as those of Example 3 were used, the mass ratio of low-activity magnesium oxide as an acid absorber and calcium oxide as a dehydrating agent was different as shown in Table 1 below.
[0073] The fluororubber sheets of Comparative Examples 1 to 5 described below were prepared by basically the same method as that of Example 1, but were different from Example 1 in the following points.
[0074] (Comparative Example 1)
[0075] In Comparative Example 1, no dehydrating agent was formulated.
[0076] (Comparative Example 2)
[0077] In Comparative Example 2, no acid scavenger was prepared.
[0078] (Comparative Example 3)
[0079] Comparative Example 3 used the same raw materials as Examples 1 and 4, but the mass ratio of the acid acceptor to the dehydrating agent was different. Specifically, the mass ratio of the acid acceptor to the dehydrating agent was set to acid acceptor:dehydrating agent=4:1.
[0080] (Comparative Example 4)
[0081] Comparative Example 4 used the same raw materials as Examples 1 and 4, but the mass ratio of the acid acceptor to the dehydrating agent was different. Specifically, the mass ratio of the acid acceptor to the dehydrating agent was set to acid acceptor:dehydrating agent=1:1.
[0082] (Comparative Example 5)
[0083] In Comparative Example 5, zinc oxide was used as an acid scavenger in addition to highly active magnesium oxide.
[0084] [Table 1]
[0085]
[0086] (parts by mass)
[0087] [Table 2]
[0088]
[0089] (parts by mass)
[0090] [Table 3]
[0091]
[0092] (Evaluation method)
[0093] The fluororubber sheets of Examples 1 to 5 and Comparative Examples 1 to 5 were subjected to corrosion tests on iron plates instead of hot plates. The test samples used fluororubber sheets with a unit weight of 680 g / m2 laminated on both the upper and lower surfaces of each fluororubber sheet. 2 The test method was to heat and pressurize the test sample continuously from top to bottom while the test sample was clamped between two iron plates. The iron plates were made of SS400 carbon steel and had a thickness of 1.5 mm and a square size of 320 mm.
[0094] The conditions for heating and pressurizing are to set the temperature to 270°C and the pressure to 2.5MPa. Under this condition, after 48 hours, samples were taken out every 24 hours to check whether the iron plate was corroded. The results are shown in Table 4 below. In Table 4, samples where no corrosion or discoloration was confirmed on the iron plate were designated as "A", samples where discoloration caused by rust was confirmed on the iron plate were designated as "B", and samples where rust progressed to the inside of the iron plate and missing parts caused by corrosion were confirmed were designated as "C". It should be noted that Figure 2 (A) shows an example of "A", Figure 2 (B) shows an example of "B", Figure 2 (C) shows an example of "C". Whether the iron plate was discolored was determined by visually observing whether the iron plate had metallic luster.
[0095] [Table 4]
[0096] Time (h) Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 48h A A A A A A A A A B 72h A A A A A B A B B B 96h A A B A B C B C C C 120h B A B B B - B - - - 144h B B B B B - C - - - 168h B B B B B - - - - -
[0097] (Measurement results)
[0098] As shown in Table 4, the iron plate is less likely to corrode in Examples 1 to 3 in which the acid absorber and the dehydrating agent are prepared at a mass ratio of acid absorber:dehydrating agent = 1:4, and Examples 4 and 5 in which the acid absorber:dehydrating agent is prepared at a mass ratio of 2:3, compared with Comparative Examples 1 and 5 in which only the acid absorber is used, and Comparative Example 2 in which only the dehydrating agent is used.
[0099] In addition, although magnesium oxide was used as an acid absorber and calcium oxide was used as a dehydrating agent, the iron plate was less likely to corrode in Examples 1 to 3 in which the mass ratio of the acid absorber to the dehydrating agent was acid absorber: dehydrating agent = 1:4 and Examples 4 and 5 in which the mass ratio of the acid absorber to the dehydrating agent was acid absorber: dehydrating agent = 2:3, compared with Comparative Example 3 in which the mass ratio of the acid absorber: dehydrating agent was 4:1 and Comparative Example 4 in which the mass ratio of the acid absorber: dehydrating agent was 1:1. It can be seen from this that the mass ratio of magnesium oxide as an acid absorber and calcium oxide as a dehydrating agent is preferably magnesium oxide: calcium oxide = 1:4 to 2:3.
[0100] The BET specific surface area of 119 m 2 / g high-activity magnesium oxide as an acid scavenger Example 1, 4 and the use of BET specific surface area of 42m 2 The iron plate is less likely to corrode than Examples 3 and 5, in which low-activity magnesium oxide of 0.1 g / g is used as an acid absorber. This shows that when magnesium oxide is used as an acid absorber, a high activity is more preferable than a low activity.
[0101] As described above, according to this embodiment, it was confirmed that the corrosion of the iron plate can be suppressed under the conditions of heating and pressurization by mixing the acid absorber and the dehydrating agent in the fluororubber. Therefore, the hot press buffer of the present invention using the fluororubber mixed with the acid absorber and the dehydrating agent can suppress the corrosion of the hot plate even when used at high temperature.
[0102] <About the stamping durability test>
[0103] Table 5 shows the results of the punching durability test of Example 6 and Comparative Example 6.
[0104] (Example 6)
[0105] The heat press buffer of Example 6 is Figure 1 The structure shown in (D) of the embodiment 6 includes two fiber-rubber composite material substrate layers (buffer body), an adhesive material layer for bonding the two substrate layers, and a surface layer (surface material) attached to the surface and back of the two substrate layers. Therefore, in order to prepare the hot press buffer of Example 6, two buffer bodies, an adhesive material, and two surface materials are prepared.
[0106] Specifically, a glass woven fabric "T860" (manufactured by Unitika Co., Ltd.) using bulked yarn as the base material of the cushioning member body was prepared. The glass woven fabric was obtained as follows: the weft yarn was a bulked yarn obtained by oversizing a twisted yarn of 305 tex composed of 3200 E glass fibers (fiber diameter 6 μm), and the warp yarn was a twisted yarn of 135 tex that was not oversized and composed of 1600 E glass fibers (fiber diameter 6 μm). The weft yarn and the warp yarn were double-woven to obtain the glass woven fabric. The weight of the glass woven fabric was 850 g / m 2 , with a thickness of 1.02 mm and a porosity of 67%. On the other hand, an unvulcanized fluororubber solution was prepared by dissolving the unvulcanized fluororubber obtained based on the formulation of Example 1 in a solvent mixed with butyl acetate, methyl ethyl ketone and acetic acid at a specified concentration. After the glass fabric was immersed in each unvulcanized fluororubber solution, it was squeezed using two rollers. Next, each glass fabric permeated with the unvulcanized fluororubber solution was fully dried to remove the solvent. In this way, two cushioning parts that became the base material layer were made.
[0107] As an adhesive material to be an adhesive material layer, a member was prepared in which the unvulcanized fluororubber prepared in Example 1 was applied to both upper and lower surfaces of a substrate made of a glass cloth having a thickness of 0.2 mm.
[0108] As the surface material to be the surface layer, a member having a glass cloth having a thickness of 0.2 mm as a base material and an adhesive based on unvulcanized fluororubber prepared in Example 1 applied to the bonding surface side and a polyimide resin applied to the surface side was used. Thus, two surface materials were prepared.
[0109] The adhesive material is sandwiched between the two layers of the buffer body, and the surface material is stacked on the surface of the upper buffer body and the back of the lower buffer body. On this basis, hot pressing is performed, and the base material layer, the adhesive material layer, and the unvulcanized fluororubber used for the surface layer are vulcanized to integrate the whole. The thickness of the hot pressing buffer of Example 6 obtained in this way is 1.9 mm.
[0110] (Comparative Example 6)
[0111] The manufacturing method of the hot press cushion member of Comparative Example 6 is basically the same as that of Example 6, but in Comparative Example 6, the unvulcanized fluororubber obtained by the formulation of Example 1 is used instead of the unvulcanized fluororubber obtained by the formulation of Comparative Example 1. The thickness of the hot press cushion member of Comparative Example 1 is 1.9 mm, the same as that of Example 6.
[0112] (Evaluation method)
[0113] For the hot pressing buffer parts of Example 6 and Comparative Example 6, a stamping durability test was carried out using a 280 mm square sample. The stamping conditions are to set the temperature to 270 ° C and the pressure to 4.0 MPa. Specifically, the hot plate was heated from 25 ° C to 270 ° C in 40 minutes, and the state was maintained for 30 minutes. Then, while maintaining the pressurized state, it was cooled by water cooling for 15 minutes. After a total of 85 minutes of pressurization, the stamping was stopped for 1 minute and released. As a stamping machine, a 150t test stamping PEWF-15045 (manufactured by Kansai Roll Co., Ltd.) was used.
[0114] The above-mentioned pressing cycle was set to 1 time, and the hot press cushioning materials of Examples and Comparative Examples were pressed before (0 time) and once, 10 times, 100 times, 200 times, 300 times, and 400 times, and the cushioning properties were evaluated at each stage.
[0115] The evaluation sample size was 25 mm φ and was selected from a 280 mm square sample that was punched under the above conditions at a position more than 5 cm away from the end. The cushioning evaluation test conditions were set at a temperature of 230°C and a pressure of 4.0 MPa. Specifically, the shock absorption rate at 0.05 kgf / cm 2 The thickness change of the evaluation sample was measured after preheating at 230°C for 2 minutes and then pressurizing at a speed of 1 mm / min until the pressure reached 4.0 MPa. As the test apparatus, an Instron universal material testing machine model 5565 (manufactured by Instron Japan Co., Ltd.) was used.
[0116] The cushioning performance was evaluated by the change in thickness from before the sample for cushioning performance evaluation was pressed to when it was pressed at 4.0 MPa. When the change in thickness (μm) was large, the cushioning performance was judged to be high, and when it was small, the cushioning performance was judged to be low. The results of the stamping durability test are shown in Table 5. It should be noted that, for the comparative example, the cushioning performance decreased significantly when the stamping was repeated 200 times, so the test was terminated.
[0117] [Table 5]
[0118]
[0119] Comparative Example 6
[0120] (Measurement results)
[0121] As shown in Table 5, the hot press cushioning member of Example 6 obtained based on the preparation of Example 1 has higher cushioning properties overall than the hot press cushioning member of Comparative Example 6 obtained based on the preparation of Comparative Example 1, and no sharp decrease in cushioning properties was observed even after 400 punchings, and high cushioning properties were maintained. On the other hand, in Comparative Example 6, the cushioning properties decreased significantly after 200 punchings. It can be seen from this that Example 6, which not only contains an acid absorber but also a dehydrating agent, can improve heat resistance compared to Comparative Example 6 containing only an acid absorber.
[0122] The embodiments and examples disclosed herein are illustrative in all points and are not restrictive. The scope of the present invention is disclosed by the claims rather than the embodiments and examples described above, and includes all modifications within the meaning and scope equivalent to the claims.
[0123] Explanation of symbols
[0124] 1A, 1B, 1C, 1D are buffer parts for hot pressing, 2 are fluororubber layers, 3 are nonwoven fabric layers, 4 are surface layers, 5 are substrate layers, 6 are adhesive layers, 11 are buffer parts, 12 are laminated plate materials, and 13 are hot plates.
Claims
1. A heat-pressing buffer comprising fluororubber, wherein: The fluororubber composition comprises a fluororubber component, a vulcanizing agent, an acid absorbent and a dehydrating agent. The amount of the dehydrating agent relative to 100 parts by mass of the total of the fluororubber component and the vulcanizing agent is greater than the amount of the acid scavenger, The total amount of the acid absorbent and the dehydrating agent is 3 to 50 parts by mass relative to 100 parts by mass of the total of the fluororubber component and the vulcanizing agent. The acid absorbent includes at least one selected from the group consisting of magnesium oxide, zinc oxide, lead oxide, dibasic lead phosphate and hydrotalcite, The dehydrating agent includes at least one selected from the group consisting of calcium oxide, aluminum oxide, magnesium sulfate, and magnesium chloride.
2. The hot pressing buffer according to claim 1, wherein: The amount of the dehydrating agent relative to 100 parts by mass of the total of the fluororubber component and the vulcanizing agent is 1.5 times or more the amount of the acid acceptor.
3. The hot pressing buffer according to claim 1, wherein: The acid absorbent is magnesium oxide, and the dehydrating agent is calcium oxide.
4. The hot pressing buffer according to claim 3, wherein: The mass ratio of the magnesium oxide to the calcium oxide is the magnesium oxide: the calcium oxide=1:4~2:
3.
5. The hot pressing buffer according to claim 3, wherein: The BET specific surface area of the magnesium oxide is 80 m 2 / g and above and 300m 2 / g or less.
6. The hot pressing buffer according to claim 1, wherein: The heat-resistant temperature of the hot-pressing buffer material is 250° C. or higher and 300° C. or lower.
